Implementation of Religious Value in the Profile of Pancasila Student in Madura - Widya Trio Pangestu; Conny Dian Sumadi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Inadequate of schools and educators is less than optimal in implementing character education and the values contained in the Pancasila principles into learning at school or personal habituation. Implementation of the Pancasila Student Profile is less than optimal. This research aims to examine the implementation of religious values in the profile of Pancasila students in elementary schools in Madura. The type of research chosen in this research is qualitative research with a qualitative descriptive approach. The aim is to describe the implementation of Religious Values in the Pancasila Student Profile in Madura. This research was conducted at several elementary schools on Madura Island, including: SDN Gili Anyar 1 Bangkalan, SDN Kamal 2 Bangkalan, SDN Buddagan 2 Pamekasan, SDN Blumbungan 3 Pamekasan. Data collection techniques through observation, interviews and documentation. The results of the research show that the implementation of religious values is carried out through activities (a) praying after and completing learning (b) memorizing short surahs before starting lessons (c) listening to chants of the holy verses of the Koran every Friday during learning activities (d) commemorating Islamic holidays (e) celebration of santri day by wearing Muslim dress.